Anxiety and depression associate with heightened risk of deep venous thrombosis: mediation through neural pathways. (14th October 2021) - Mezue, K; Osborne, M T; Abohashem, S; Zureigat, H; Abbasi, T; Gharios, C; Cardeiro, A; Akuffo, E; Pitman, R; Shin, L; Jaffer, F; Rosovsky, R; et al.
Abstract: Background: Anxiety disorders and depression associate with an increased risk of deep venous thrombosis (DVT). However, it is unclear if this association persists after robust adjustment for confounders. Further, the mechanism mediating this potential link remains unknown. Prior studies show that anxiety and depression associate with heightened stress-associated neural activity (notably in the amygdala: AmygA), which in turn promotes chronic inflammation, a driver of thrombosis syndromes. Purpose: To evaluate whether the association between anxiety/depression and DVT risk: A) persists after robustly accounting for potential confounders, and B) is mediated by upregulated stress-associated neural activity (namely AmygA). Methods: Data were obtained from the Mass General Brigham Biobank, which included detailed health information on 118 871 adult participants. A subset of 1520 study subjects underwent clinical 18F-fluorodeoxyglucose positron emission tomography imaging during the follow up period, from which AmygA was measured as the ratio of amygdalar to regulatory (ventromedial pre-frontal cortex) activity. International Classification of Disease (ICD) codes in the medical record were used to define anxiety disorders, depression, and lower extremity DVT. Individuals on anticoagulant therapies for atrial fibrillation prior to enrolment and/or imaging were excluded. Cox analysis were performed wherein patients who developed DVT prior to Biobank enrolment (2599 subjects) were excluded. Mediation analysis was used to examine the role of AmygA in mediating the link between anxiety/depression and DVT. Results: The median age of the study population was 57 years [interquartile range (IQR) 28] and 58.4% were female. DVT occurred in 1231 participants (1.2%) over a median follow up period of 3.3 years (IQR 3.0). Cox regression analysis showed that anxiety disorders and depression were independent predictors of incident DVT after controlling for confounders (Table 1; p<0.0001 for all analyses). In the subset of 1383 participants who underwent brain imaging, anxiety disorders and depression associated with increased AmygA activity after controlling for risk factors including age, sex, Charlson index, hormone use and cancer history (standardized β [95% CI]: 0.124 [0.017–0.232], p=0.023 and 0.151 [0.041–0.260], p=0.007 respectively). Further, AmygA associated with DVT (odds ratio (OR) [95% CI]: 1.248 [1.064–1.465], p=0.007). Path analysis demonstrated that increased AmgyA mediated the effect of both anxiety and depression on DVT (log OR [95% CI]: 0.0256 (0.0009–0.0592), p<0.05 and 0.0314 (0.0033 to 0.0718), p<0.05 respectively, Figure 1). Conclusion: Anxiety disorders and depression associate with an increased risk of DVT via a mechanism that includes heightened stress-related neurobiological activity. Future studies should evaluate whether modulating this neural pathway could reduce the incidence of DVT. Funding Acknowledgement: Type of funding sources: None.